Allelopathic Influence Of Excoecaria Agallocha L. On Seed Germination And Seedling Growth Of Some Pulses And Millets - KAVITHA.D.,; PRABHAKARAN.J,; K.ARUMUGAM, (International Journal of Pharma and Bio Sciences, 2012)
Excoecaria agallocha L. also known as milky mangrove and ‘Blind-Your-Eyes’-belonging to Euphorbiaceae family commonly grown in the mangrove forest of Pitchavaram, Tamil Nadu,south India was tested for its allelopathic potential against seed germination and early seedling growth of green gram (Vigna radiata (L.)R. Wilczek.),Black gram (Vigna mungo (L.)Hepper),groundnut (Arachis hypogaea L.), pearlmillet (Pennisetum typhoides St.& Hub.) and fingermillet (Eleusine coracana Gaertn.).Green house experimental studies were conducted in plastic pot with normal field soil for the evaluation of germination and growth attributes of crop plants by applying various concentrations (2,5,10,15,20 and 25%) of leaf extracts of E.agallocha. The results showed that the germination percentage was gradually decreased, seedling lengths also affected in all the five crops from lower concentration to higher concentrations of leaf extracts. The fresh and dry weight, Chlorophyll, aminoacid and protein contents of crop seedlings were decreasing with increasing concentration of leaf extracts.The inhibitory effect was concentration dependent.The results clearly indicated that the leaf extracts of E. agallocha exhibited strong inhibitory effects on the germination and growth parameters of millets than pulses.